BIO-MARKERS ASSAY IN ACUTE MYOCARDIAL INFARCTION- A CROSS SECTIONAL STUDY - DR. M. GANESH; DR. SUBHA PALANEESWARI . M; DR. T. KARTHIKEYAN (International Journal of Pharma and Bio Sciences, 2013)
Acute myocardial infarction (AMI) is diagnosed with history of chest pain, ECG, enzyme bio markers. Many persons may not present with typical chest pain and have atypical presentations. The aim of the present study was to study the levels of various enzymatic markers in AMI and determine the efficacy of CK-MB in terms of early detection when compared to that of the other know routine enzymatic markers of AMI. The present study included 50 cases with AMI and 40 control subjects. We observed that within six hours of hospital admission, cases with AMI showed a significant increase of both Total CK and CK -MB.